Розробка системи керування тягового асинхронного електроприводу на основі нейромережі - Кириленко, Ярослав Олександрович; Воробйов, Богдан Віталійович; Сенченко, Сергій Олександрович; Кутовий, Юрій Миколайович; Хань, Лю (Національний університет "Чернігівська політехніка", 2023)
У статті представлено результати науково-методичного дослідження синтеза нейромережевого контролера та розрахунок умов виникнення фрикційних автоколивань в електроприводі рейкових транспортних засобів таких як: магістральні електровози, електропоїзди приміського сполучення, шахтні електровози, трамваї, поїзди метро та інші види транспорту. Проведені дослідження показали можливість побудови інтелектуальних систем управління, на базі прямо спрямованих нейронних мереж з сигмоїдальними активаційними функціями нейронів прихованого шару структури NN3-20-1. Такі системи, на відміну від класичних, мають хороші демпфуючими властивостями, що перешкоджає виникненню коливальних або автоколивальних динамічних режимів. Застосування нейронних мереж для управління електромеханічними системами не призводить до підвищення астатизму по впливу, що збурює, тому в даній системі спостерігається статична помилка швидкості другої маси, яка становить 0,7%.

The article examines the synthesis of a neuro-boundary controller and the development of minds in the culprit of frictional auto-switches in the electric drive of railway transport vehicles such as mainline electric locomotives, municipal electric trains, mine electric locomotives, trams, metro trains and other types of transport. Slippage of locomotive wheels and frictional self-oscillations worsen a number of operational and energy indicators of railway transport. Therefore, the development of modern management systems that eliminate these problems is an urgent task. The purpose of the article is to study the two-mass elec tromechanical system of the DS3 mainline electric locomotive, to identify the conditions under which self-oscillation is excited in it, and to synthesize a neuroregulator that ensures the elimination of self-oscillating modes for any combination of electric drive parameters. The investigations showed the feasibility of intelligent control systems based on direct neural measurements of the sigmoidal activation functions of the neurons of the attached ball structure NN3-20-1. Such systems, in contrast to the classical ones, have good damping power, which overcomes the disadvantage of columbing or autocolumn dynamic modes. Transient processes of the speed of the second mass of the traction asynchronous electric drive of the DS3 electric locomotive with a neural network control system are presented. Since, during the training of the neural network, the necessary restrictions of the coordinates of the electric drive, caused, for example, by the electronic and mechanical strength of the drive, were not taken into account. The tightening of neural circuits for controlling electromechanical systems does not lead to an increase in astatism in the flow that boils, so in this system a static reduction in the liquidity of another mass, which becomes 0.7%, is avoided.
Design of the control system of tractional asynchronous electric drive based on neurocontroller
Keywords: нейромережева система керування; генетичний алгоритм; асинхронний двигун; електропривод; перехідний процес; характеристика зціплення; neuro-fusing system; genetic algorithm; asynchronous motor; electric drive; transition process; clutch characteristic